Studies on Current Status of Hypertension Prevalence, Awareness, Treatment in Jiangxi Province, China - Zehui Jiang; Jun Zhang; Junyong Wang; Junshan Li; Meihui He; Yuanan Lu (Journal of Hypertension and Cardiology, 2020)
Objective To understand the present status of high blood pressure in Jiangxi adults including the prevalence rate, overall awareness, and hypertension treatment. Methods a total of 7,200 adult participants (over 18 years old) lived in Jiangxi were recruited using a stratified sampling method. Blood pressure was measured for all the participants and a questionnaire survey was conducted. A 24-hour urine sample was also collected to understand urine sodium and potassium levels. Results Our findings revealed that the measured systolic blood pressure (SBP) and diastolic blood pressure (DBP) were 125.9 mmHg (95% CI, 124.85-126.95) and 79.2 mm Hg (95% CI, 78.15-80.25). The prevalence of hypertension among the enrolled adults was 27.43% (95% CI, 26.38%–28.48%). Among the affected participants, less than 30% of them (95% CI) were aware of their hypertension condition, and only 28.56% (95% CI) were under anti-hypertension medications. The mean salt intake converted from urinary sodium was 10.92±4.07 g and the mean±SD of 24-h urinary sodium and potassium excretion were 185.51±65.44 mmol and 25.98±9.16 mmol, respectively. The high-salt condiments was determined to be the main source of sodium in the region. Conclusion Findings from this study form the baseline information to understand the hypertension condition in the region and indicate a possible solution for hypertension prevention through avoiding high-salt condiments.
Keywords: hypertension